Liminal spaces and call for praxis(ing) - Espinosa-Dulanto, Miryam; Humpal, David L; Pitre, Leilya; Santana, Jolanta Smolen (Curriculum and pedagogy series., 2013)
Liminal Spaces and Call for Praxis(ing) follows the theme of the Curriculum & Pedagogy conference that highlighted issues of power, privilege, and supremacy across timelines and borders. This volume comprises of an interconnected mosaic of theoretical research and praxis. Facing the current and future challenges of corporatization of education, it becomes imperative to identify and deconstruct elements that provide more responsive and fertile ground for a research and praxis based mosaic of pedagogy. This volume includes works of those scholars who identified or worked with communities of color and/or who drew on the activist and intellectual traditions of peoples of color, third world feminism, indigenous liberation/sovereignty, civil rights, and anticolonial movements.